INFANT AND YOUNG CHILDREN FEEDING PRACTICES AND NUTRITIONAL STATUS OF TRIBAL CHILDREN - M. SARADA DEVI, M.DEEPA and (The Journal of Research, PJTSAU, 2019)
Nutritional status of children is directly affected by infant and young child feeding practices below two years of age, ultimately impacts survival. The ideal food for the young infant is human milk which has the specific characteristics that match the growing infants’ nutritional requirements. Cross sectional study was carried out to know the infant and young child feeding practices in Mahabubnagar district of Telangana state, which is major cause for latter development of children. Purposive random sampling technique was used to select the subjects for the study. Subjects for the study comprised of 120 members. Mothers with youngest child in the age group of 4 – 24 months were included in the study. Simple descriptive statistics was used for analyzing the results. The study revealed that young children feeding practices and diet during pregnancy were the major contributing factors for malnutrition among the children. Forty per cent of the mothers are ignorant about the importance of colustrum, 63 per cent of mothers have low awareness on timely initiation of breast feeding, 43 per cent of mothers were unaware of type of foods to be given and initiation time weaning. Only 7 per cent tribal women initiated breast feeding within one hour. Forty per cent of children were in mild nutritional status. Prevalence of malnutrition was due to delayed initiation of supplementary foods. Malnutrition continues from infancy and it effects child growth and development in latter stages of life.